Photometric Stereo Techniques for the 3D Reconstruction of Paintings and Drawings Through the Measurement of Custom-Built Repro Stands - Marco Gaiani; Elisa Angeletti; Simone Garagnani (Heritage)
In the digital 3D reconstruction of the shapes and surface reflectance of ancient paintings and drawings using Photometric Stereo (PS) techniques, normal integration is a key step. However, difficulties in locating light sources, non-Lambertian surfaces, and shadows make the results of this step inaccurate for such artworks. This paper presents a solution for PS to overcome this problem based on some enhancement of the normal integration process and the accurate measurement of Points of Interest (PoIs). The mutual positions of the LED lights, the camera sensor, and the acquisition plane in two custom-designed stands, are measured in laboratory as a system calibration of the 3D acquisition workflow. After an introduction to the requirements and critical issues arising from the practical application of PS techniques to artworks, and a description of the newly developed PS solution, the measurement process is explained in detail. Finally, results are presented showing how the normal maps and 3D meshes generated using the measured PoIs’ positions, and further minimized using image processing techniques, which significantly limits outliers and improves the visual fidelity of digitized artworks.